Penerapan Surat Dakwaan oleh Jaksa Penuntut Umum Berdasarkan Hukum Positif Indonesia - Freddy Simanjuntak; Dianita Eka Hutabarat; Widya Estella; Dendy Natalius Purba (DOKTRINA: JOURNAL OF LAW, 2020)
An indictment is a letter made or prepared by the public prosecutor attached when submitting a case file to the court containing the name and identity of the criminal when and where the act was carried out carefully and clearly regarding the act committed. The purpose of this study is to understand the application of the indictment by the public prosecutor based on positive Indonesian law. The research method used by the writer is a descriptive analytical method, which is a research method that illustrates and explains the topic or title as well as the problems that arise from the topic through a literature study. will cause the defendant to be released from all charges or result in the cancellation of the indictment itself. The Public Prosecutor must pay attention to the selection of the indictment and editorial technical forms.